Development of Drug and Food Surveillance Databases at Port Health Office - agnes anaike putri; arief hargono (Universitas Airlangga, 2019)
Background: Recently the data of drug, food, cosmetics, medical devices, and addictive materials surveillance use a simple database system. However, this sample has major weakness in entry data processing which in turn causing a lot of errors and delayed data report. Purpose: This study aims to develop drug, food, cosmetics, medical devices, and addictive materials surveillance database to be more accurate, fast, and generate more information. Method: This study is an observational descriptive study. This research was conducted in January-February 2018 at the port health office class 1 of Surabaya. The population used in this study 6 officers of the port health office. The type of data used is primary data by conducting in-depth interviews. This research was conducted in two steps, namely logic design (data normalization, relationship design with entity relationship diagrams, and dictionary creation) and physical planning (the database design using Epi info for Windows software). The database testing was carried out by two officers in the field of quarantine control and epidemiology surveillance, to assess the ease, accuracy, timeliness, and completeness of the information produced. Results: The results showed that the trial process makes the officers easier to input data. This trial also simplifies and shortens the time of the surveillance officer in conducting data analysis. This condition promotes the report qualities (accurate, timeliness, and complete information). Conclusion: The use of epi info software can reduce the risk of data entry errors, be more accurate, faster, and the results of the analysis produced are more varied.